Evaluation of nurses’ practices toward orthopaedic wound infection - bader, Thair; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To evaluate of nurses practice toward orthopaedic wound infection and to determine the relationship between orthopaedic nurses practice and their demographic data characteristic Methodology: A descriptive study was carried out at orthopaedic wards of Baghdad Teaching Hospital started from February 1 st, 2011 to August 30th, 2011. A non-probability sample of (39) orthopaedic nurses who were working in orthopaedic wards were selected from Baghdad Teaching Hospital. The data were collected through the use of questionnaire , which consists of two parts (1)Demographic data form that consists of a(10) items and (2) orthopaedic nurses practice form that consists of (4)sections contain (69) items, by mean of direct observe technique with orthopaedic nurses. The validity of the questionnaire was determined through presenting it to (20) specialist expert and its reliability were determined through a pilot study which was carried out through the period from April 1st, 2011 to June 15th, 2011. Descriptive statistical analysis procedures (frequency, percentage, mean of score) and inferential analysis procedures (person correlation coefficient, contingency coefficient) were used for the data analysis. Results: The findings of the study indicated that the orthopaedic nurses have inadequate or deficit in some aspects relative to wound infection in orthopaedic wards. No significant relationship was found between orthopaedic nurses practice and their gender, years of employment in nursing field, years of experience in orthopaedic wards and duration of the training session, while a significant relationship was found between orthopaedic nurses practice and their age, marital status, level of education, sharing in training session and the number of training session that orthopaedic nurses were engaged it. Recommendations: The researcher recommend that special training session , concerning wound infection and standards orthopaedic nurses practice toward wound infection control that should be followed in orthopaedic wards ,and booklets should be designed and presented all orthopaedic nurses, in addition to make a new study that can evaluate orthopaedic nurses knowledge concerning wound infection control in orthopaedic wards.